Pengetahuan Astronomi Orang Muna di Desa Kasaka Kecamatan Kabawo Kabupaten Muna - Tasrudin . (Laboratorium Jurusan Antropologi, Fakultas Ilmu Budaya, Universitas Halu Oleo, 2017)
Astronomical knowledge is one form of knowledge that is still owned by Muna People and always make this Astronomical knowledge as a benchmark in various daily activities, therefore in this study aims at describing the forms of knowledge of Astronomy, its function and inheritance in Muna society particularly the society who is domiciled in Kasaka Village, Kabawo District which is the location of this research. This research uses qualitative descriptive method, data collection is done by observation involved, in-depth interviews with informants and through documents relating to knowledge of Astronomy of Muna people. Data were analyzed as qualitative descriptive consisting of data reduction, data presentation and conclusion. Based on the results of research and finding of data in the field at the time of the research, can be disclosed various facts related to Astronomical knowledge, there are some forms of knowledge that Astronomy still apply in the midst of Muna society such as early determination of planting (agriculture), the reading of natural phenomena constellation of stars observations (maritime fields), the determination of certain days which are time well spent to develop an activity and the use of calendars based on the Islamic calendar, all of which serve for safety in all affairs. Keywords: knowledge, astronomy, Muna people